Battery Charging Control Using Photovoltaic with Sepic Converter - Ika Putri, Ratna; Nata, Surya; Priyadi, Bambang (International Journal of Frontier Technology and Engineering, 2022)
This article presents a battery charging design using photovoltaic with a septic converter. The use of batteries as energy storage is one way to ensure the availability of energy to the load and overcome the weaknesses of photovoltaic systems which depend on solar irradiation and temperature. when the solar irradiation is low, the battery can supply energy to the load. SEPIC converter is used to adjust the battery charging voltage requirements. The output voltage of the SEPIC converter is maintained constant by setting the duty cycle using a microcontroller. Based on the results of experimental testing, this PV system with a SEPIC converter can work well. Battery charging can be done optimally. This system is also equipped with automatic disconnection of the battery if the battery is fully charged so that the lifetime of the battery is maintained